Linear control systems: with MATLAB applications - Manke, B.S (Khanna Pub, 2005)
Linear control systems: with MATLAB applications / Manke, B.S.. -- Delhi: Khanna Pub, 2005 629.8312 M279e8 8th ed. No. of Copies : 1